Toxicity of Aluminum to Ceriodaphnia dubia in Low‐Hardness Waters as Affected by Natural Dissolved Organic Matter. (21st August 2019) - Besser, John; Cleveland, Danielle; Ivey, Chris; Blake, Laura
Abstract: We conducted a series of 7‐d toxicity tests with Ceriodaphnia dubia in dilutions of low‐hardness natural waters, which contained dissolved organic carbon (DOC) concentrations up to 10 mg/L. Stream waters were mixed with well water to achieve 2 target hardness levels (20 and 35 mg/L) and 4 DOC concentrations. Tests with aluminum (Al)‐spiked waters were conducted in a controlled CO2 atmosphere to maintain the pH at a range of 6.0 to 6.5. The results were used to estimate effect concentrations for survival and reproduction, expressed as total (unfiltered) Al concentrations. There were small differences in total‐Al thresholds between waters with 20 and 35 mg/L hardness, but effect concentrations for C. dubia survival (median lethal concentrations) and reproduction (effect concentrations, 20%) increased log‐linearly with increasing DOC concentrations in the range, 0.3 to 6 mg/L. Slopes of these regressions were similar to slopes from data used to revise the US Environmental Protection Agency water quality criterion for Al, but toxic effects in the present study occurred at total‐Al concentrations 8‐ to 10‐fold greater than toxicity values used for criteria development. This difference probably reflects the long equilibration (aging) times of Al test waters used in the present study (up to 192 h) compared with short (3‐h) equilibration times in other studies used for criteria development. These results confirm the importance of DOC as a control on Al toxicity in low‐hardness waters, but they also demonstrate that total‐Al concentrations are not predictive of Al toxicity, except under defined water quality (pH, hardness, DOC) and exposure conditions (e.g., aging of test waters). Environ Toxicol Chem 2019;38:2121–2127. Published 2019 Wiley Periodicals, Inc. on behalf of SETAC. This article is a US government work, and as such, is in the public domain in the United States of America.